The reader in the structure of Russian prose by H. Kvitka-Osnov’ianenko - Кириченко, Юлія Сергіївна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2017)
The implicit reader of first-person narration in the Russian prose by H. Kvitka-Osnov’ianenko is explored in this article. It is shown that the author’s point of view was heavily influenced by the ideas and esthetic theories of Enlightenment. Connection between the author’s point of view and S. Uvarov’s Official Nationality doctrine has been revealed. It is indicated that the author perceives the reader as a real person which can be influenced by the text as well as a noetic instance. The social characteristics of implicit reader are described.